213 Can Styloid Process and Internal Carotid Artery Anatomy Be Used to Predict Carotid Artery Dissection?. (12th October 2021) - Cruddas, L; Joffe, M; Baker, D
Abstract: Aim: Carotid artery dissection is a common cause of stroke in the young. It has been related to the association of the carotid artery with fixed neighbouring anatomical structures. This study assesses the association between styloid process length, internal carotid artery position and cervical carotid artery dissection (CCAD). This information would provide potential predicative radiological measurements, which could prevent delays in CCAD diagnosis. Method: Retrospective data was collected from two central London hospitals over five years. CCAD cases were identified from individuals who underwent computer topography angiography (CTA) of the neck for suspected CCAD. The following data was collected: evidence of CCAD; bilateral styloid process length and presence of styloid-hyoid ligament calcification; bilateral styloid process-internal carotid distance; calcification of carotid arteries and whether their position was aberrant. Cases were dissection-side, age and gender matched with two non-dissection controls. Results: Three hundred and fifty-five individuals were identified. Fifty individuals had CCAD, of which 4 had bilateral dissection. In individuals with CCAD, average styloid process length was 27.5mm and styloid process-internal carotid distance was 5.14mm. There was no significant association between styloid process length or styloid process-internal carotid distance, and CCAD when compared with matched controls. Internal carotid artery aberrancy was significant for non-dissection. Conclusions: In this study, there was no association between styloid process length and styloid process-internal carotid distance with CCAD. These measurements cannot be used to predict the possibility of a CCAD following trauma.